Investigation of 1200 V SiC MOSFETs’ Surge Reliability - Huan Li; Jue Wang; Na Ren; Hongyi Xu; Kuang Sheng (Micromachines, 2019)
In this work, the surge reliability of 1200 V SiC metal-oxide-semiconductor field-effect transistors (MOSFETs) from various manufactures has been investigated in the reverse conduction mode. The surge current tests have been carried out in the channel conduction and non-conduction modes. The experimental results show that the maximum surge currents that the devices can withstand are similar for both cases. It is found that short circuits occurred between the gate and the source in the failed devices. The characteristics of the body diode have also changed after the tests. By measuring the device characteristics after each surge current is applied, it can be concluded that the damages to the gate oxide layer and the body diode occurred only when the maximum surge current is applied. By decapping the failed devices and observing the cross section of the damaged cell, it is found that high temperature caused by excessive current flow through the devices during the surge tests is the main reason for the device failure. Finally, the TCAD simulation of the devices has been carried out to bring insight into the operation of the devices during the surge events.